The impact of movements in the wrong learning to learn the correct movements of free swimming - Naji, diaa (Journal of Physical Education, 2012)
The know Ledge of The Type of Relationship Between The high speed and kip the ball will hales the teachers to identify the term of the training course and good components according to his scientific information . the aims of research are *know the reaction of nigh speed and kip the boll in soccer.*know the reaction of the high speed and kite the ball in soccer.The subject of the study consist of (10)pupils in physical Education for university of Baghdad